The Effect of Website “Remaja Cegah DBD” on the Prevention Behaviour of Dengue Haemorrhagic Fever Among Students at Junior High School in Makassar City, Indonesia - Syahrir, Wahyunita; Wahiduddin, Wahiduddin; Arsin, A. Arsunan; M. Thaha, Ida Leida; Stang, Stang (International Journal of Statistics in Medical Research, 2025)
Background: Dengue Haemorrhagic Fever (DHF) is an acute infectious disease caused by the dengue virus. It occurs frequently children and adolescents. In 2023, the incidence of DHF in Makassar City was 26 per 100,000 population. Preventive efforts, such as increasing community awareness through health education at the school level, need to be initiated. Objectives: The aim of this study was analyze the effect of the "Remaja Cegah DBD" (Youth Prevents DHF) website on dengue prevention behavior among students at Public Junior High School (SMPN) in Makassar. Methods: This study was a quasi-experimental design with a non-randomized pre-test and post-test control group design involving 122 students, the main intervention group consisted of 61 respondents at SMPN 8, and the comparison intervention group included 61 respondents at SMPN 6. Data were collected from August 22 to September 6, 2024. Data analysis was conducted using univariate and bivariate methods, including Paired t-test, Wilcoxon test, Independent t-test, and Mann-Whitney test, with Stata Program version 14. Results: There was a significant difference in DHF prevention knowledge before and after the website intervention (p=0.000). There was also a significant difference in attitudes (p=0.000) and practices (p=0.000) before and after the website intervention. Furthermore, there were significant differences in prevention behavior between the main intervention group (website) and the comparison group (leaflet), with statistical test results for knowledge (p=0.000), attitude (p=0.000), and practice (p=0.0016). Conclusion: Website was more effective as an educational prevention of DHF among adolescents or students in Makassar City, compared to leaflet-based media.